PERAN PERSEPSI HARGA DALAM MEMEDIASI PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus pada Miniso di Kota Denpasar) - Putra, Putu Aditya Wijaya; Seminari, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
This research was conducted at Miniso Denpasar City. The purpose of this study is to explain the effect of brand image and Purchase Decision of on Consumer Purchase Decisions at Miniso in Denpasar City. This study uses the theory of consumer behavior with a sample of 100 people and uses a purposive sampling technique. Data collection in this study was carried out by observation and questionnaire methods This study uses the Classical Assumptions Test technique, Path Analysis and Sobel Test. Based on the results of this study, the results obtained are that brand image has a positive and significant influence on consumer purchasing decisions, brand image has a positive and significant influence on price perceptions, price perceptions have a positive and significant influence on consumer purchasing decisions and brand image has a positive and significant influence on consumer purchasing decisions through price perceptions. The implications of this research for development strategies can be used by Miniso Denpasar City in developing appropriate strategies according to consumer behavior patterns.